Intellectual Capital in Learning Organizations - Vashishtha, S. D.; Sharma, Priti (Prabandhan: Indian Journal of Management, 2012)
Educational Institutions having a proper check on the management of their intellectual capital are enjoying better status in the market. It has been proven many times that by virtue of physical and financial capital, no organization can survive in the market. It is the intellectual capital or the intangibles which work as value enhancers in an organization and aid in the organization attaining great heights in the market. In learning organizations, where input and output both are intangibles. Intellectual capital is the main input, output and value driver of it. Since there is little research in this field, so with the help of this treatise, an attempt has been made by the authors to accentuate the composition of intellectual capital in learning organizations and the relevance of the management of intellectual capital in learning organizations.